S. mansoni SmKI-1 Kunitz-domain: Leucine point mutation at P1 site generates enhanced neutrophil elastase inhibitory activity. - Fábio Mambelli; Bruno P O Santos; Suellen B Morais; Enrico G T Gimenez; Duana C Dos S Astoni; Amanda D Braga; Rafaela S Ferreira; Flávio A Amaral; Mariana T Q de Magalhães; Sergio C Oliveira (Public Library of Science (PLoS), 2021)
The Schistosoma mansoni SmKI-1 protein is composed of two domains: a Kunitz-type serine protease inhibitor motif (KD) and a C-terminus domain with no similarity outside the genera. Our previous work has demonstrated that KD plays an essential role in neutrophil elastase (NE) binding blockage, in neutrophil influx and as a potential anti-inflammatory molecule. In order to enhance NE blocking capacity, we analyzed the KD sequence from a structure-function point of view and designed specific point mutations in order to enhance NE affinity. We substituted the P1 site residue at the reactive site for a leucine (termed RL-KD), given its central role for KD's inhibition to NE. We have also substituted a glutamic acid that strongly interacts with the P1 residue for an alanine, to help KD to be buried on NE S1 site (termed EA-KD). KD and the mutant proteins were evaluated in silico by molecular docking to human NE, expressed in Escherichia coli and tested towards its NE inhibitory activity. Both mutated proteins presented enhanced NE inhibitory activity in vitro and RL-KD presented the best performance. We further tested RL-KD in vivo in an experimental model of monosodium urate (MSU)-induced acute arthritis. RL-KD showed reduced numbers of total cells and neutrophils in the mouse knee cavity when compared to KD. Nevertheless, both RL-KD and KD reduced mice hypernociception in a similar fashion. In summary, our results demonstrated that both mutated proteins showed enhanced NE inhibitory activity in vitro. However, RL-KD had a prominent effect in diminishing inflammatory parameters in vivo.